Family caregivers challenges about caring for children with impaired skin integrity - Ayana Carolina Gonçalves Teixeira Matos; Evanilda Souza de Santana Carvalho; Silvia da Silva Santos Passos; Rudval Souza da Silva (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objective: To know the challenges of family caregivers members for the maintenance of care for children with impaired skin integrity after hospital discharge. Method: This is a qualitative study of action research, developed from March to July of 2017. Participants were ten family/caregivers of the children with impaired skin integrity. The data obtained through interviews were submitted to content analysis. Results: The family caregivers of the child with impaired skin integrity received guidelines for home care at discharge, experienced feelings of relief, getting out of the hospital and, for fear of causing physical and emotional damage, sought help in the services and neighborhood, overprotected the child, to avoid complications and readmission, and faced the lack of resources to care for. Conclusion: Maintenance of care for children with impaired skin integrity after hospital discharge requires application of measures of protection from skin wounds, constant surveillance of the child in order to prevent local traumas and infections, and the search for support in the Health, to obtain material resources and guidelines for care.